HEAVY METAL ACCUMULATION IN ROAD SIDE VEGETATION OF URBAN AREAS OF KARACHI (Biological Sciences - PJSIR, 2001)
Lead and heavy metal accumulation in the tarry deposits on the leaves of trees and shrubs grown along road side of urban area has been determined. Samples of leaves were collected in summer and winter. Pb, Cu, Mn and Zn were analysed from the tarry deposit. The range of average concentration of lead was around 250 to 1155 ppm, copper around 845 to 100 ppm, manganese 171 to 650 ppm and zinc 103 to 706 ppm . The gravitational sedimentation and impact on vegetation of coarse fraction is responsible for high lead contamination. Areas of greater traffic density have vegetation with higher lead levels.The data collected shows that almost all the pollutants are being generated by automobile exhaust in the urban area of Karachi .